Media Education: History and Prospects of Development in Uzbekistan (Eurasian Journal of Humanities and Social Sciences, 2023)
The article discusses the relevance and importance of media education in the modern world, traces the stages of its development in Uzbekistan. And also given practical recommendations for the introduction of media education in the system of continuous education of the republic.